Imports and welfare: variety losses of the Argentine crisis of 2001-2002 - Brambilla, Irene (2011)
The access to a large variety of products is one of the main sources of gains from international trade and globalization. When an economy goes through a crisis, aggregate demand shrinks resulting in fewer product varieties being imported. In this paper we quantify short-run and medium-run welfare losses that resulted from the reduction in the number of imported product varieties during the Argentine crisis of 2001-2002. We find that short-run welfare losses vary widely across products and that medium-run recovery depends on the ability to substitute towards new varieties.